New Treatments for Bacterial Keratitis - Raymond L. M. Wong; R. A. Gangwani; Lester W. H. Yu; Jimmy S. M. Lai (Journal of Ophthalmology)
Purpose. To review the newer treatments for bacterial keratitis. Data Sources. PubMed literature search up to April 2012. Study Selection. Key words used for literature search: “infectious keratitis”, “microbial keratitis”, “infective keratitis”, “new treatments for infectious keratitis”, “fourth generation fluoroquinolones”, “moxifloxacin”, “gatifloxacin”, “collagen cross-linking”, and “photodynamic therapy”. Data Extraction. Over 2400 articles were retrieved. Large scale studies or publications at more recent dates were selected. Data Synthesis. Broad spectrum antibiotics have been the main stay of treatment for bacterial keratitis but with the emergence of bacterial resistance; there is a need for newer antimicrobial agents and treatment methods. Fourth-generation fluoroquinolones and corneal collagen cross-linking are amongst the new treatments. In vitro studies and prospective clinical trials have shown that fourth-generation fluoroquinolones are better than the older generation fluoroquinolones and are as potent as combined fortified antibiotics against common pathogens that cause bacterial keratitis. Collagen cross-linking was shown to improve healing of infectious corneal ulcer in treatment-resistant cases or as an adjunct to antibiotics treatment. Conclusion. Fourth-generation fluoroquinolones are good alternatives to standard treatment of bacterial keratitis using combined fortified topical antibiotics. Collagen cross-linking may be considered in treatment-resistant infectious keratitis or as an adjunct to antibiotics therapy.